Disparities in Sex-Specific Arrest Rates: Does Offense Type and Neighborhood Context Matter? - Chamberlain, Alyssa W. (Crime & delinquency, 2024)
We investigate differential effects of neighborhood structure on the arrest rates of men versus women. Given potential disparities in the use of discretion by offense severity, we disaggregate crime to aggravated assaults, burglaries, and drug offenses. We employ negative binomial regression models to predict the number of arrests by sex for each crime type, and test for significant differences within and between sex across offense severity. We find few differences within and across sex, however, levels of disorder and the racial composition of a neighborhood are important structural factors in understanding arrests by sex and across offense type. Neighborhood composition is associated with differential rates of arrest by sex and across offense severity, which has implications for gender disparities in the criminal justice system.